STUDY OF THE DEMAND LEVEL FOR SPARE PARTS IN AUTO SERVICE ENTERPRISES (Spectrum Journal of Innovation, Reforms and Development, 2025)
The article presents the results of modeling the need for spare parts using adaptive mathematical models for the formation of the need for spare parts of car service enterprises, the emergence, randomness, and distribution patterns of the need for spare parts during maintenance and repair of vehicles, and forecasting.